Digital activism and cyberconflicts in Nigeria : occupy Nigeria, Boko Haram and mend - Olabode, Shola Abidemi (Emerald Publishing Limited, 2018)
This book offers an innovative contribution to the literature on digital activism and cyberconflicts. Analysing sociopolitical and ethnoreligious conflicts within an African-centred context, the author uses Nigeria as a lens to understand the digital and organisational aspects of digital media uses in the Occupy Nigeria movement protest, the Boko Haram conflict and The Movement for the Emancipation of the Niger Delta (MEND) conflict. Timely, in a period of intense conflict across the globe, the author employs an interdisciplinary approach, drawing on the Cyberconflict Framework to examine conflicts emerging in computer-mediated environments. Examining the implications for socio-political and economic reform and change, the cases explored provide a snapshot of the emerging digital culture of conflict. The book contributes to existing knowledge by bridging the gap in the literature on digital activism and conflict as a field of study.
Keywords: Internet and activism -- Nigeria.; Protest movements -- Nigeria.; Social media -- Political aspects -- Nigeria.; Language Arts & Disciplines, Communication Studies.; Communication studies.; elektronické knihy; electronic books